Khithbah dalam Pernikahan Perspektif Pendidikan Islam dan Psikologi - Ais Surasa; Irfan Fahmi; Encup Supriatna; Husain Husain (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The engagement (khitbah) is a crucial step before marriage. It is a formal statement made by a man to a woman he is proposing to marry. This statement can be made directly or through an intermediary. After the engagement, the marriage can be continued, or it can be postponed. Delaying marriage is permissible for those who are unable to marry, but those who are able are encouraged to do so immediately. The values of Islamic education are the development of human reason and the regulation of behavior and emotions based on Islamic teachings. Thus, Islamic educational values will bring happiness, prosperity, and salvation to humans both in this world and the hereafter. According to Islam, everyone must prepare themselves as well as possible to build relationships based on love and noble values. Physical, mental, and economic readiness are required; in this situation, in terms of the educational characteristics inherent in Islamic teachings, the goal is to build a safe, pleasant, and peaceful household environment.